Critical Level of Chromium for Rice in Different Soil Type - Hidayatuz Zu'amah; Sukarjo Sukarjo; Elisabeth Srihayu Harsanti; Siska Apriyani; Baiq Nunung Sulastri (School of Postgraduate Studies, Diponegoro Univer, 2023)
The increasing number of industries and poor treatment of waste will damage environmental health, including agricultural land. Agricultural products from contaminated soil may contain hazardous heavy metals such as chromium which can be harmful to human health if consumed. Examination and determination of chromium critical level in paddy soil are required to evaluate the threshold of heavy metals to disable to distribute into paddy plants. This study aims to obtain the critical level of chromium in light and heavy textured soils with paddy as a plant indicator. The pot experiment was carried out at the greenhouse using a completely randomized design with two factors are heavy metal concentration (Cr) and soil texture (A) and five times repeated. The chromium adsorption test uses the Langmuir approach method. Chromium sorption in heavy-textured soil is higher than in light-textured soil. The maximum sorption of chromium metal in light-textured soil is 87.719 mg kg-1, while in heavy-textured soil is 204.082 mg kg-1. Total chromium in the soil decreases after harvest and reduces rice yields. The critical level of light-textured soil chromium in rice was 0.861 mg kg-1, while the critical level for heavy-textured soil Chromium in rice was 1.012 mg kg-1.